Spinal muscular atrophy type II (intermediary) and III (Kugelberg-Welander): evolution of 50 patients with physiotherapy and hydrotherapy in a swimming pool Atrofia muscular espinhal tipo II (intermediária) e III (Kugelberg-Welander): evolução de 50 pacientes com fisioterapia e hidroterapia em piscina - Márcia C. B. Cunha; Acary S. B. Oliveira; Rita Helena D. D. Labronici; Alberto Alain Gabbai (Arquivos de Neuro-Psiquiatria)
We added hydrotherapy to 50 patients with spinal muscular atrophy (SMA) who were being treated with individual conventional physiotherapy. Hydrotherapy was performed at an approximate temperature of 30 degrees Celsius, twice a week, for thirty minutes in children and for forty-five minutes in adults during a 2-year period. The outcome derived from this combined modality of treatment was rated according to physiotherapeutic evaluations, the MMT (Manual Muscular Test), and the Barthel Ladder. Patients were reevaluated at 2-month intervals. After two years of ongoing treatment, we were able to observe that the deformities in hip, knee and foot were progressive in all SMA Type II patients, and in some Type III. Muscle strength stabilized in most SMA Type III patients, and improved in some. MMT was not done in SMA Type II. In all patients we were able to detect an improvement in the Barthel Ladder scale. This study suggests that a measurable improvement in the quality of daily living may be obtained in patients with SMA Types II and III subjected to conventional physiotherapy when associated with hydrotherapy. A hidroterapia foi realizada em SO pacientes com atrofia muscular espinhal, os quais foram também tratados com fisioterapia individual convencional. O tratamento hidroterápico foi realizado em piscina aquecida numa temperatura de aproximadamente 30° Celsius, duas vezes por semana, durante 30 minutos em crianças e 45 minutos em adultos num período de dois anos. Os benefícios deste tipo de tratamento foram avaliados de acordo com a evolução clínica, o MMT(Teste de Força Muscular) e a Escala de Barthel. Os pacientes foram reavaliados a cada dois meses. Após dois anos de tratamento nós observamos que as deformidades nos quadris, joelhos e pés foram progressivas em todos os pacientes do Tipo II e em alguns do Tipo III. Houve estabilização da força muscular na maioria dos pacientes com SMA Tipo III, e melhora da força em alguns; nos pacientes com SMA Tipo II este teste não pode ser realizado. Em todos os pacientes pudemos verificar melhora em realção à Escala de Barthel. Este estudo sugere que houve melhora destes pacientes com SMA Tipos II e III em relação as atividades de vida diária quando a fisioterapia convencional foi associada a hidroterapia.